AKMEOLOGIYALÍQ JANTASÍW TIYKARÍNDA DENE TÁRBIYASÍ OQÍTÍWShÍLARÍNÍŃ TÁLIM-TÁRBIYA PROCESIN JOYBARLASTÍRÍW - Utepbergenov, A.K. (SCIENCE and SOCIETY, 2025)
This article analyzes the features of designing the educational process of physical education teachers based on the acmeological approach. The main principles are considered of acmeology and their significance in the formation of professional competence of physical education teachers. Methods of effectively organizing are also analyzed the educational process through innovative technologies and an individual approach.